Relações entre educação e saúde: formação continuada para o enfrentamento da situação de morte por profissionais de enfermagem - Gianini, Marcelo Márcio Siqueira (2012)
This research emphasizes the discussion of the topic of death; although death often occurs in hospitals, we do not see people thinking about its significance in their lives and the professionals who participate daily in this process are not prepared to deal with this situation. It is also common that professionals do not even recognize their own feelings while witnessing the death of their patients. The understanding of this experience is essential for the formation of professionals who, in addition to technical knowledge, should know how to handle their own emotions, accepting the feelings of patients, family and coworkers. This work aimed to investigate a training course to cope with the situation of death that contributes to the cognitive-affective interface; it aimed at health professionals, especially the nursing staff who deal daily with dying patients. The chosen method was the participatory action research; themes and lessons were developed from the needs presented by the participants. The procedures were: initial interview, application of Maslach´s Burnout Inventory (1996) before and after the course, the course itself, course evaluation questionnaire, analysis and discussion of results. The course improved not only the personal and professional development of these professionals, as well as proved to be a means of coping in relation to burnout, allowing the reduction of the levels of emotional distress (33%), job dissatisfaction (33%) and depersonalization (58 %). Nurses working with terminally ill people really need resources to collaborate effectively in the preparation of the meaning of these experiences of illness and death, which generate emotional overload and that must be addressed by ongoing formative processes